Science in a Radical Sense - Duica, William (2001)
Since the debate about the nature of scientific theories has been held in the context of the scheme-content dualism, philosophers from the most different traditions have had to face, sooner or later, the dilemma between realism and relativism. I shall argue that following Davidson's criticism against the so-called "third dogma" it is possible to find a way-out of this dilemma. This paper is an attempt to look at the meaning of the scientific language from the point of view of radical interpretation. The radical element of interpretation will join the conception of scientific theortes in order to supersede false alternatives in the light of a definitton of science in a radical sense.